Does bite force provide a competitive advantage in shrews? The case of the greater white‐toothed shrew. (14th January 2015) - Cornette, Raphaël; Tresset, Anne; Houssin, Céline; Pascal, Michel; Herrel, Anthony
<x xml:space="preserve">Abstract</x> Competition for resources has long been considered a major driver of evolution by natural selection. Thus, the ability to gain access to resources not available to other individuals and species should be under strong selection. In the present study, we focus on the potential role of biting in a shrew (Crocidura russula) because this trait may confer two advantages: (1) a broadening of the dietary niche and (2) the provision of direct superiority in interspecific interactions. The model chosen is the greater white‐toothed shrew, which is considered as invasive in northern Europe and which is also known to displace native species of shrew in this area. Moreover, its distribution appears to constrain the distributional ranges of other species of shrew in the Maghreb. We use geometric morphometrics and a simple biomechanical model to describe shape variation and to evaluate the mechanical potential of the mandible of ten species of white‐toothed shrews, with a special emphasis on C. russula and Crocidura suaveolens. We find that C. russula possesses an intermediate mechanical potential linked with an intermediate level of shape variability. Our results suggest that the higher mechanical potential may explain the observed pattern of colonization of the Atlantic islands by C. russula at the expense of C. suaveolens. Finally, our results also suggest that the ability to bite hard may be under strong selection in shrews. © 2015 The Linnean Society of London, Biological Journal of the Linnean Society, 2015, 114, 795–807.